A Civil War journal a collection of little-known facts and other odds-and-ends about the Civil War - Nofi, Albert A. (New York Promontory Press, 1995)
Provided by Evelyn Kading Clark Trust
Originally published in 1993 by Combined Books under title: The Civil War notebook.
Keywords: United States -- History -- Civil War, 1861-1865 -- Miscellanea. United States